1992
DOI: 10.1007/bf02035133
|View full text |Cite
|
Sign up to set email alerts
|

Acute infection of mice with highly virulent group B streptococci as a host resistance model for immunotoxicity assessment

Abstract: This report describes a unique model for immunotoxicity evaluation in mice. The model is adapted from previously described mouse models for group B streptococcus (GBS) infections in human neonates. In this disease as well as a number of human diseases caused by highly virulent pathogens, the mechanisms of innate immunity are unable to protect the host, and survival is strictly dependent on acquired immunity. Unlike other host resistance models widely used in immunotoxicity studies, the GBS model utilizes bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One of the most important aspects of resistance to this organism is the ability to produce opsonizing and complement-fixing Abs (23,(53)(54)(55). DEX at dosages of 0.1 mg/kg/day and greater significantly suppresses the IgG Ab response to a model T-dependent Ag (SRBC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most important aspects of resistance to this organism is the ability to produce opsonizing and complement-fixing Abs (23,(53)(54)(55). DEX at dosages of 0.1 mg/kg/day and greater significantly suppresses the IgG Ab response to a model T-dependent Ag (SRBC).…”
Section: Discussionmentioning
confidence: 99%
“…This time frame was selected because it was consistent with the 16-day dosing protocol used in most other experiments in this study and because a preliminary experiment indicated that the peak IgG response to SRBC occurs on day 16 (22). Host resistance assays; resistance to streptococcus group B. B6C3F 1 mice have little innate resistance to these bacteria (the LD 50 is ϳ5 bacteria/ mouse), but resistance increases substantially if the mice are immunized with heat-killed streptococcus group B bacteria (23). Resistance in this model is mediated by Abs, complement, and phagocytic cells (23).…”
Section: Immunological and Host Resistance Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations